2019
DOI: 10.3889/oamjms.2019.035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Breast Milk Nutrition on Serum Insulin-Like Growth Factor-1 in Preterm Infants

Abstract: BACKGROUND:Insulin-like growth factor 1 (IGF-1) is one of the essential intrauterine hormonal mediators of growth, and its serum values are often low after preterm delivery.AIM:To evaluate the influence of immediate breast milk feeding on serum IGF-1 in preterm newborns.SUBJECTS AND METHODS:This prospective, observational cohort study included 60 premature infants born < 32 weeks of gestation, divided into group A and B regarding breastfeeding or formula feeding. Growth measurements were taken at birth. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Delayed myelination is observed in Fmr1 KO mice [ 30 , 31 ], and genetic reduction of insulin-like growth factor receptor-1 (IGF-1R) or treatment with a synthetic analog of a naturally occurring neurotropic peptide derived from IGF-1 corrects a multitude of disease phenotypes in Fmr1 KO mice [ 32 , 33 ]. Breast milk has a higher quantity of human IGF-1 than bovine milk or infant formula [ 34 ] and is associated with elevated IGF-1 in preterm infants [ 35 ] and altered white matter volume in boys [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed myelination is observed in Fmr1 KO mice [ 30 , 31 ], and genetic reduction of insulin-like growth factor receptor-1 (IGF-1R) or treatment with a synthetic analog of a naturally occurring neurotropic peptide derived from IGF-1 corrects a multitude of disease phenotypes in Fmr1 KO mice [ 32 , 33 ]. Breast milk has a higher quantity of human IGF-1 than bovine milk or infant formula [ 34 ] and is associated with elevated IGF-1 in preterm infants [ 35 ] and altered white matter volume in boys [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…114 As yet, no study has reported an antepartum or postpartum method which prevents or diminishes the development of classical autism in the infant other than prolonged breastfeeding from birth exclusively. 76,83,84,[115][116][117] Although the pathologic processes in autism begin around birth, behavioral symptoms usually do not appear until ages 1-4 years. This could portend the futility of IGF-1 administration to psychologically symptomatic autistic patients, once the malady is well established.…”
Section: Challengementioning
confidence: 99%
“…These anti-inflammatory cytokines could potentially lower the relatively pro-inflammatory state in the immature gut and consequentially increase IGF-1 levels. In one study, preterm infants who received own mother's milk from birth were shown to have higher levels of IGF-1 at term equivalent age compared to those who were formula fed from birth [26]. Moreover, animal studies found that in a state of inflammation or nutrient deprivation, parenteral feeding was associated with lower IGF-1 levels compared to enteral feeding.…”
Section: The Route Of Nutrient Administrationmentioning
confidence: 99%